O-013 Safety and efficacy of MCA M2 thrombectomy in delayed time window (>6 hours): a propensity score analysis from the STAR registry. (23rd July 2022) - Limaye, K; Koo, A; de Havenon, A; Al Kasab, S; Bohnstedt, B; Maier, I; Psychogios, M; Wolfe, S; Arthur, A; Dumont, T; Kan, P; De Lacey, R; et al.
Abstract : Background: The safety and efficacy of mechanical thrombectomy (MT) for the M2 segment of the middle cerebral artery (MCA) has been shown to be effective and safe in recent post-hoc or observational studies. There is, however, no known benefit to MT for the M2 segment in the delayed time window (>6 hours). Here, we perform a propensity score analysis of MT for MCA M1 and M2 segments in a delayed time window using the multi-national, multi-institutional (Stroke Thrombectomy and Aneurysm Registry) STAR registry to test the safety and efficacy of MT in this patient population. Methods: The STAR registry is a prospective, multicenter, non-randomized observational study registry for acute ischemic stroke thrombectomy and aneurysm treatment. We analyzed all patients who underwent MT within a late time window (>6 hours from onset) involving isolated M1 or M2 occlusions. Patients with missing clinical outcomes were excluded. Each center independently collected basic demographics, medical history, comorbidities, baseline functional status (using the modified Rankin scale, mRS), details of presentation (including the NIHSS), details of the MT (including location and technique), clinical outcomes, and complications. Unbalanced cohorts with a nonrandom distribution of patients between the cohorts were accounted for by using propensity score (PS) matching. After PS-matching, all variables were compared again using univariate hypothesis tests between the isolated M2 and PS-matched M1 cohorts to determine whether the PS-matching algorithm yielded balanced comparison groups. Results: Of 1083 consecutive patients analyzed, propensity matching yielded 180 well matched M1 and M2 pairs; the remaining 723 patients were discarded from the analysis. Baseline demographics were well balanced between the groups (M1 and M2). ASPECTS score 7.6 ± 1.7 versus 8.3 ± 1.5, P<0.001 was higher in the M2 group. Intravenous thrombolysis (IV tPA) use was numerically higher in the M2 group but did not reach statistical significance 20.0 versus 23.3; P=0.522. Procedural technique (ADAPT, Stent-retriever, Solumbra), thrombectomy duration 35.2±25.3 versus 36.1±28.8; P=0.754 and the number of passes 2.3±2.1 versus 2.3±1.7; P=0.978 were similar in both groups. Final mTICI score 2b/2c/3 26.7/12.2/46.1 versus 38.3/13.3/38.9; P=0.053 were not significantly different. Post-procedural asymptomatic hemorrhage rates were similar 29.4 versus 27.8; P=0.816, but symptomatic hemorrhage rates were higher in the M1 group 7.2 versus 2.2; P=0.047. Rates of good clinical outcome (mRS 0–2) were similar at 3 month follow-up43.9% versus 46.7%; P=0.672. The overall mortality was similar between the cohorts (12.8% versus 13.9%; P=0.877) Conclusion: In the STAR registry, M2 occlusions achieved similar rates of recanalization and good functional outcome compared to M1 occlusions. There was less symptomatic intracranial hemorrhage in the M2 compared to M1 group in the delayed time window (>6 hours). Analysis of the STAR registry, a large multinational and multi-institutional database, shows a relatively generalizable result for safety and efficacy of M2 thrombectomy in a delayed time window. Disclosures: K. Limaye: None. A. Koo: None. A. de Havenon: None. S. Al Kasab: None. B. Bohnstedt: None. I. Maier: None. M. Psychogios: None. S. Wolfe: None. A. Arthur: None. T. Dumont: None. P. Kan: None. R. De Lacey: None. J. Osbun: None. P. Jabbour: None. A. Rai: None. M. Park: None. J. Mascitelli: None. M. Levitt: None. A. Poflika: None. W. Cassagrande: None. S. Yoshimura: None. R. Williamson: None. B. Gory: None. M. Mokin: None. I. Fragata: None. D. Romano: None. S. Chowdry: None. D. Behme: None. A. Spiotta: None. C. Matouk: None.